Fatigue life enhancement of additive manufactured 316l stainless steel by LSP using a DPSS laser system. (1st February 2022) - Zulić, Sanin; Rostohar, Danijela; Kaufman, Jan; Pathak, Sunil; Kopeček, Jaromir; Böhm, Marek; Brajer, Jan; Mocek, Tomáš
ABSTRACT: Present work aims to study the fatigue life behaviour of additively manufactured (AM) stainless steel 316L in a laser shock peening (LSP) process. The fatigue behaviour of as-built samples and LSPeened sample were studied on the AM samples. A new diode-pumped laser system was utilized as an instrument to perform LSP operations. LSP operation was performed under two different sacrificial layers of different materials i.e. vinyl tape and aluminium tape. The other essential LSP parameters, namely energy, pulse width, spot size, overlap, and number of layers were kept constant based on the previous experimental findings. The characterization was done for analyzing the residual stresses using a hole drilling process, and a 4-point bending machine. A considerable improvement in compressive residual stress and fatigue life was observed in the LSPeened samples. Such improvements in residual stresses and fatigue life may pave a road to establishing diode-pumped lasers for LSP applications.